ANALISIS SEMIOTIKA ROLAND BARTHES MAKNA KURSI KOSONG TAYANGAN MATA NAJWA EDISI MENANTI TERAWAN - Rista Mala; Umi Rahmawati; Dian Novitasari (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2021)
The Coronavirus disease (Covid-19) pandemic has an impact on changes in Indonesia and even the world. The increasing number of patients who are positively exposed to the virus is making people